Toilet Training Methods for Toddlers and Preschool-Age Children: A Scoping Review of Current Evidence - Dewi, Kurnia Meishinta; Rakhmawaty, Windy; Mardhiyah, Ai (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Independence in toileting is a skill that must be achieved throughout the stages of child growth and development. Toilet training (TT) is an important part of child development that can increase independence and minimize disturbances in bowel and bladder control in children. In general, this exercise is performed on children aged 12-36 months (toddlers) and children aged 48-60 months (preschool) depending on each child's readiness. This readiness is commonly shown by the emergence of a child's instinct to defecate or urinate independently. In this process, parents and caregivers play an important role in stimulating independence in children through TT. Unfortunately, most parents and caregivers may find it difficult to initiate, instruct, guide, and demonstrate TT for their child. This review aims to evaluate the effectiveness and applicability of various TT methods based on recent evidence. This review uses the scoping review design by including 3 databases in the search strategy: EBSCO-host, PubMed, and Scopus. All keywords used are synthesized from the PICO were “Toddlers” AND “Preschool Children” OR “Preschool Child” AND “Toilet Training” OR “Potty Training” AND “Toileting”. This study only reviews the results of primary studies from the past five years (2018-2023), published in English or Bahasa, and with experimental designs. Children with a history of functional gastrointestinal and urinary tract disorders were excluded from the study. The methodological validity and risk bias of each study is included in this review using the Joanna Briggs Institute (JBI) instrument. The main findings in this review study indicate that there are 7 types of toilet training interventions that have been developed and implemented. There are The AAP Guideline, The DAP Guideline, The Application of TT, AI Technology, Storytelling Treatment, Hypnoparenting, and TT Demonstration. Findings show that most interventions focus on individual or group settings with additional techniques like demonstration and storytelling. Parents and caregivers, including pediatric nurses, can consider TT method adapted from The AAP Guideline to improved toilet training process among toddlers and preschool-age children.